1958
DOI: 10.1063/1.1744340
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Association of Methanol Vapor

Abstract: The absorption of infrared radiation by methanol vapor in the region 3200 to 3800 cm-1 has been studied at 305° and 335°K as a function of vapor density. The results best correlate with the model that methanol vapor is composed of monomer, dimer, and tetramer, with little or no trimer present. The heat of dissociation of the dimer is found to be approximately 3 kcal/mole, and that of the tetramer approximately 17 kcal/mole. The greater stability of the tetramer compared to the dimer is consistent with a cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

1960
1960
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…We have not performed a full vibrational analysis and therefore the computation of the 0-H frequency on the basis of,fo,, alone would be premature. We note, however, that the vapor phase frequency of vo, is 3682 cm-' (53). Matrix isolation of (CH,OH)l yielded values of 3490-3528 cm-' dependent on the type of matrix used (24) whereas the lowest OH-frequency in the solid is 3187 cm-' (9).…”
Section: Results and Discussion I (Ch$oh)mentioning
confidence: 99%
“…We have not performed a full vibrational analysis and therefore the computation of the 0-H frequency on the basis of,fo,, alone would be premature. We note, however, that the vapor phase frequency of vo, is 3682 cm-' (53). Matrix isolation of (CH,OH)l yielded values of 3490-3528 cm-' dependent on the type of matrix used (24) whereas the lowest OH-frequency in the solid is 3187 cm-' (9).…”
Section: Results and Discussion I (Ch$oh)mentioning
confidence: 99%
“…In other words, why are isovolume compositions so effective in breaking up ring structures? In an effort to answer this question let us follow arguments supposing that ring structures are present predominantly in the form of dimers [30], trimers [31], or tetramers [32].…”
mentioning
confidence: 99%
“…The spectrum shape and its peak positions were essentially identical to those known for ϳ10 Ϫ4 mol/l methanol vapor at an ambient temperature. 24,4,25,26 There were also weak absorptions between 1900 and 2600 cm Ϫ1 associated with phonon bands of the diamond windows and a C-O stretch overtone. 27 We stress here the good quality of our IR spectra obtained at such a high temperature.…”
Section: Methodsmentioning
confidence: 99%
“…3 Around the same time, the first IR studies of hydrogen-bonding interactions in pure methanol vapor showed the existence of equilibria between methanol monomer, dimer, and tetramer forms as a function of vapor density. 4 Nowadays, a huge number of different experimental and theoretical studies devoted to the hydrogen-bonded structure of methanol in different phases can be found in the literature. Summarizing the accumulated theoretical and experimental knowledge, the models of the hydrogen bonding between methanol molecules in different phases can be represented as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation